RANCANG BANGUN ALAT UKUR TINGGI BADAN OTOMATIS BERBASIS ANDROID - Diva Perdana; Fitria Priyulida (JURNAL MUTIARA ELEKTROMEDIK, 2019)
Design and construction of an Android-based automatic height measurement tool has been carried out. This research was made due to the demand for sophisticated medical support equipment with all the capabilities it has that continues to develop so that effective and efficient medical support equipment can be produced. This tool is designed with the aim of providing information about the measurement data of height and weight to users. Measurement results data will be sent to Android in the form of messages to be stored using the android database system storage.This research method uses qualitative methods, namely: study literature and literature and conduct experiments on the circuit design made, then test the function of the tool with a meter to determine the accuracy of the work of this tool. This tool is made by utilizing the sharp ir sensor as conversion then will sent via GSM SIM 800L, and the data is displayed via the application and SMS on the patient's AndroidThe test results show that the distance obtained is the conversion result taken from the travel time of infrared rays when they emit light and receive reflected objects. seen the percentage error value for each measurement, which allows the sensor to read errors and possible interference from the compiler program. As long as the% error does not exceed 3%, the module design for automatic height measuring instruments can be used properly